2002
DOI: 10.1292/jvms.64.673
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antigenic Proteins of Housedust Mites in 90 Dogs Suffering from Atopic Dermatitis.

Abstract: ABSTRACT. Housedust mites, Dermatophagoides pteronyssinus (D. pteronyssinus) and Dermatophagoides farinae (D. farinae), are the important causative agents of allergic diseases in human and animals. By using 165 dogs suffering from atopic dermatitis (AD), serum levels of immunogloblin E (IgE) antibody against 25 kinds of allergen including housedust mites were determined. Housedust mites were the most frequent allergen against which 90 of the 165 allergic dogs (54.5%) by IMMUNODOT assay. With the further analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 17 publications
5
29
1
Order By: Relevance
“…These results mirror those of previous testing in European and American dogs, studies that used either purified group 1 and 2 allergens, or whole mite extracts . In contrast to these early observations, there are higher Der f 1 and Der f 2 IgE seropositive reactions in mite allergic dogs in Japan . That Der f 2 is an important and relevant mite allergen in Japanese atopic dogs is also supported by the rapid and robust response of Df/Der f 2‐reactive dogs to immunotherapy performed with high doses of the single and pullulan‐conjugated allergen Der f 2 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results mirror those of previous testing in European and American dogs, studies that used either purified group 1 and 2 allergens, or whole mite extracts . In contrast to these early observations, there are higher Der f 1 and Der f 2 IgE seropositive reactions in mite allergic dogs in Japan . That Der f 2 is an important and relevant mite allergen in Japanese atopic dogs is also supported by the rapid and robust response of Df/Der f 2‐reactive dogs to immunotherapy performed with high doses of the single and pullulan‐conjugated allergen Der f 2 .…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, of 16 Japanese atopic dogs with IgE against Df, six (38%) had positive IgE to Der f 1 and seven (44%) binding Der f 2 . Other Japanese authors subsequently reported that 44 and 74% of 90 HDM‐reactive dogs had IgE antibodies that recognized Der f 1 and Der f 2, respectively . The latter observations suggested that Der f 2 was a major Df allergen for dogs in Japan.…”
Section: Introductionmentioning
confidence: 98%
“…7 Der f 2 and Der p 2 are major allergens of the D. farinae and D. pteronyssinus house dust mites that have been shown to be major allergens in dogs, although additional allergens may be implicated. 9 Allermmun â HDM (Nippon Zenyaku Kogyo Co. Ltd. (ZENOAQ), Tokyo, Japan), is an immunotherapeutic agent composed of recombinant Der f 2 protein conjugated with pullulan (Der f 2-P) and is commercially available in Japan. Pullulan is a large polysaccharide polymer secreted by Aureobasidium pulllans and used in various pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…That 75% of Japanese atopic dogs sensitized to the Dermatophagoides farinae house dust mite (HDM) have IgE against Der f 2, provides a rationale to develop and test adjuvanted AIT against this single allergen.…”
Section: Introductionmentioning
confidence: 99%